Kant Meets Cyberpunk. - Schwitzgebel, Eric (Disputatio: International Journal of Philosophy, 2019)
I defend a how-possibly argument for Kantian (or Kant*-ian) transcendental idealism, drawing on concepts from David Chalmers, Nick Bostrom, and the cyberpunk subgenre of science fiction. If we are artificial intelligences living in a virtual reality instantiated on a giant computer, then the fundamental structure of reality might be very different than we suppose. Indeed, since computation does not require spatial properties, spatiality might not be a feature of things as they are in themselves but instead only the way that things necessarily appear to us. It might seem unlikely that we are living in a virtual reality instantiated on a non-spatial computer. However, understanding this possibility can help us appreciate the merits of transcendental idealism in general, as well as transcendental idealism's underappreciated skeptical consequences.